Akun Instagram Lambe Turah sebagai Media Informasi dan Bisnis Perspektif Teori Industri dan Ayat Muamalah - Bustanul Karim; Ika Ariyati; Eka Prasetiawati (KURAS Institute, 2023)
The role of social media as a medium for sharing status, photos, and videos has turned into a business tool. There are few accounts on behalf of individuals or organizations. However, the account manager is anonymous, such as the Lambe Turah account, which is the object of research in this article. This paper aimed to analyze Lambe Turah's account based on industry and Muamalah's theory. This paper used a type of qualitative research. Data collection was carried out using the note-taking technique. Data analysis was carried out using descriptive-analysis techniques through the selected theory. The study results show that Lambe Turah's Instagram account is a news account on social media that provides factual and non-factual information for financial gain, so it can be classified as non-journalist media. In the muamalah aspect (socio-economic), the sources of information presented by the Lambe Turah account are not listed as validity indicators. This information related to the news on the account cannot be used as the primary reference. In the view of Ayat Muamalah, the validity of information is the main requirement for the eligibility of information to be reported and disseminated. Therefore, the efforts made by Lambe Turah as a provider of information and business services have yet to be guided by the production principles discussed in the Qur'an.